2019
DOI: 10.1590/0034-7167-2018-0649
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of health of users with HIV/AIDS in a specialized service

Abstract: Objective: to understand the perception of users of a Specialized Care Service (SAE- Serviço de Assistência Especializada) in HIV/AIDS about their oral health. Method: qualitative research that used the techniques of participant observation and focal group. For the analysis of the material produced, categories of analysis, construction of dialogical map and identification of linguistic repertoires were used. Results: impacts arising from oral health problems such as: inability to eat properly, feeling ashame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…One emerging explanation for this association is interpersonal discrimination; however, scholarly work linking discriminatory experiences with oral health is still scant and fragmented. Based on previous reviews 16,25 we identified the publications summarized in Table 1 10,26–45 . All studies have addressed interpersonal discrimination, and only one study tested specific hypotheses based on an intersectional perspective.…”
Section: Existing Research Exploring Oppression and Oral Health Inequ...mentioning
confidence: 99%
See 1 more Smart Citation
“…One emerging explanation for this association is interpersonal discrimination; however, scholarly work linking discriminatory experiences with oral health is still scant and fragmented. Based on previous reviews 16,25 we identified the publications summarized in Table 1 10,26–45 . All studies have addressed interpersonal discrimination, and only one study tested specific hypotheses based on an intersectional perspective.…”
Section: Existing Research Exploring Oppression and Oral Health Inequ...mentioning
confidence: 99%
“…Based on previous reviews 16,25 we identified the publications summarized in Table 1. 10,[26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45] All studies have We argue, then, that the persistence of oral health inequities over time and across space has much to do with how we employ these categories in our scientific, clinical and policy endeavours. 30,46 Understanding oppression in its structural forms requires attention to how the social, political, commercial/corporate and behavioural determinants intersect and impact oral health outcomes.…”
Section: E Xis Ting Re S E Arch E Xploring Oppre Ss I On and Or Al He...mentioning
confidence: 99%
“…Oral candidiasis interferes negatively with the quality of life (QoL) of people living with HIV/AIDS. [18][19][20]61,62…”
Section: Discussionmentioning
confidence: 99%
“…One commonly used tool is the Oral Health Impact Profile 14 (OHIP-14). [17][18][19][20][21][22] The 14 questions were grouped into seven functional domains: limitations, physical pain, psychological discomfort, physical disabilities, psychological disabilities, social disabilities, and handicaps, and were analyzed for each domain. The answer options for each item were: hardly ever, very often, fairly often, sometimes, and never/ do not know, and were coded as 4, 3, 2, 1, and 0.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation